The social and psychological effects of those infected with the Corona pandemic and the role of clinical social service in confronting it - Al-Otaibi, Nahar Ali (Journal of Humanities & Social Sciences, 2022)
The study aims to know the social and psychological effects of those infected with the Corona pandemic and the role of clinical social service in confronting it in the hospitals of the city of Makkah for the year 1443. two classes; For a sample of people infected with the Corona pandemic in Makkah hospitals, their number is (150) according to the variables of gender, age, housing, marital status, educational qualification, number of family members and family income level. Social status and monthly income. The study reached a set of results, most notably: One of the most important social effects on the injured are (physical distancing imposed by precautionary measures, preventing family visits as a result of injury, limiting the interaction of family members with the patient), and the results also showed that the The most important psychological effects of the injured are (fear of losing my relatives as a result of being infected with the Corona virus, feeling of constant anxiety due to the control of thoughts of infection with Corona, and the occurrence of obsession with personal hygiene). The Corona pandemic is (encouraging social initiatives in support of medical institutions, mitigating the effects of social distancing, raising their morale, and providing advice to reduce their anxiety). The study recommended the need to hold more awareness campaigns, communication and visit to the families of patients to educate them about the patient’s psychological condition after his recovery, and how to deal with him so that he can engage in a normal life again, and work to provide financial support for families low and no income; Encouraging community members to participate in community development programs to confront this pandemic.